FAKTOR-FAKTOR YANG BERPENGARUH PADA KEPUASAN KERJA AUDITOR (Studi Empiris pada Kantor Akuntan Publik di daerah Semarang) - Rizky Ariawan Ramadan; Darsono Darsono (Diponegoro Journal of Accounting, 2015)
The     purposefrom     this     research     is     examining     the     influence     ofOrganizationalCommitment,      Professional      Commitment,      Job      Autonomy      andOrganizational-Professional Conflict (OPC) on Auditor’s Job Satisfaction.The population of this research is auditors that work in publicaccountant firm located at Semarang, The sample taken from 45 auditorsfrom 8 public accountant firm at Semarang. Method of data collection in thisresearch is using questionnaire. Method of data   analysis   is   reliability   and   validityanalysis,   classic   assumption   analysis   and hypotheses analysis is using linearregression analysis.The result indicates all variables reliable, valid and fulfil classic assumption. Theresult of hypotheses analysis are Organizational Commitment has positive influence but not significantly on job satisfaction, Professional Commitment has positive influence and significantly on job satisfaction, Job  Autonomy has positive influence and significantly on job satisfaction and OPC has negative influence and significantly on job satisfaction.